ANALISIS WACANA INTERAKSI KELAS BAHASA GURU DALAM PEMBELAJARAN AL-QURAN MELALUI MEDIA DARING - Fathul Khair Tabri , (JOEL: Journal of Educational and Language Research, 2022)
The purpose of this study was to find out and analyze the discourse on the interaction of the teacher's language class in Wafa learning through online media in class II E SDIT Al-Fatih Makassar City. The method used in this study is a qualitative descriptive method. The data in this study are in the form of teacher utterances used when teaching and learning in the classroom by paying attention to the discourse of class interaction in the form of transactions, exchanges, and actions. Data collection techniques using recording techniques. The data analysis technique in this study was carried out through the following steps: (1) data transcription, (2) data classification, (3) data interpretation, and (4) data conclusion. Checking the validity of the data is done by member checking or checking with the respondent. The results of the research found are the discourse of class interaction in the form of transactions, exchanges, and actions. In the discourse of transactions, three types of transactions were found, namely information transactions, directive transactions, and inducement transactions. In exchange discourse, one type of exchange is found, namely boundary exchange. In the discourse of action, there are thirteen types of acts, namely markers, introductions, provocations, examinations, directives, informative, encouragement, instructions, confessions, answers, approvals, metastatements, and conclusions.